2017
DOI: 10.1108/jchmsd-08-2014-0030
|View full text |Cite
|
Sign up to set email alerts
|

Conservation planning of built heritages of Old Dhaka, Bangladesh

Abstract: Purpose Built heritage is a unique resource, an irreplaceable expression of the richness and diversity of our past and of the generations who have gone before us. Old Dhaka has an outstanding built heritage that is of significance not only in the local, but also in a national and regional context. But senseless urbanization and ignorance of such an important issue in the existing detailed area plan is destroying the built heritages of Dhaka. As a result, many heritage buildings of Dhaka have been destroyed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…It is appropriately directing decisions on their maintenance interventions in the form of the sustainable repair approach. Huq et al (2017) suggested that the current condition of the built heritage commonly point out for appropriate maintenance interventions. This appropriate maintenance interventions are parallel with the conceptual model of "Green Maintenance".…”
Section: Jchmsd 93mentioning
confidence: 99%
“…It is appropriately directing decisions on their maintenance interventions in the form of the sustainable repair approach. Huq et al (2017) suggested that the current condition of the built heritage commonly point out for appropriate maintenance interventions. This appropriate maintenance interventions are parallel with the conceptual model of "Green Maintenance".…”
Section: Jchmsd 93mentioning
confidence: 99%
“…Bangladesh is not an exception. Heritage conservation is a fairly new concept in the country, with various isolated experiments for the preservation of heritage sites being carried out, but with inadequate frameworks and guidelines, and lacking specialized conservation strategies (Huq et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The phrase “architectural heritage” relates to terms like “built heritage” (Archaeological Services Inc, 2012), “cultural built heritage” (Dutta and Husain, 2009), “architectural built heritage” (Vodopivec et al , 2014), “historical buildings” (Kutut et al ., 2014), “monuments” (Torre, 2002), “a building associated with some events and personality” (Huq et al , 2017). Architectural heritage (AH) not only considers the esthetic value and historical value of the built form but also includes the economic, environmental, social and cultural benefits.…”
Section: Introductionmentioning
confidence: 99%
“…and proceeds along with site and surrounding (settings or precinct) unchanged with the current state, i.e. the level of originality retained by the AH siteKalman (1980),Parker (1986), Heritage Council of WesternAustralian (1991), Brampton Flower City (2000,Stewart and Kalman (2004),Neale (2011),Vodopivec et al (2014),Gang et al (2015) andHuq et al (2017) Social accessibilityThe degree to which AH may be accessed and experienced by a diverse group of people socially or culturallyDutta and Husain (2009) and Kutut et al (2014) Social compatibility AH has socially compatible reuse without hampering the previous ethnic value Kalman (1980) and Townsend et al et al (2000), Vodopivec et al (2014), Bakri et al (2015) and Fitri et al (2015) Traditional value Direct or indirect transmission of customs or beliefs (Odishan dance, Chittrapat painting, dressings, etc.) other than religious ones, from generation to generation by the AH ICOMOS (1999), Global Heritage Fund (2009), UNESCO (2012) and Fitri et al (2015) Trends/ patterns/ themes AH was built during a particular dynasty with specific trends/patterns/ themes, i.e.…”
mentioning
confidence: 99%